Characteristics of State in Islamic Perspective: Review of the Application of Islamic Law in the Indonesian Legal System - Zainal Abidin Muhja; Arifin Faqih Gunawan; Erman I Rahim; Sardjana Orba Manullang; Chami Yassine (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2024)
This study aims to analyze the characteristics of state according to Islamic paradigm and the ideal form of relationship between religion and state in the Indonesian constitution. The main focus is on how the integration between religion and the state is manifested in these two contexts, as well as how Pancasila, as the ideology of the Indonesian state, plays a role in finding a balance between religious diversity and democratic principles. This research uses a normative legal method with a philosophical and analytical approach. Through analytical descriptive analysis, this study describes the prevailing laws and regulations, legal theory, and positive law enforcement practices related to this issue, both in the context of Islam and within the framework of the Indonesian constitution. The results show that state concept in Islam tends to maintain a strong integration between religion and state. Meanwhile, in the Indonesian context, Pancasila as a state ideology serves as a meeting point that accommodates diversity and democratic principles. This study reveals that despite the challenges, the compromise found in Pancasila has been a solution to maintain the unity of Indonesia in the midst of its religious and cultural diversity